Semi-nomadism in southern Israel today - Berman, Mildred (Annals of the Association of American Geographers, 1967)
(Abstracts of the papers presented at the 62nd annual meeting of the Association of American Geographers, Toronto, Ontario, Canada, August 29–31, 1966)
Keywords: dept.egm

Dimensions of east African cultures - Good, CM [Review] - Stolberg, I (Professional Geographer, 1967)
Keywords: dept.egm; ⛔ No DOI found